Assessing visual control activities in ceramic tile surface defect detection: an eye-tracking study. (2017) - Ulutas, Berna; Ozkan, N. Firat
Digital cameras and image processing algorithms may be helpful in inspection and classification of ceramic tiles in a production line. However, worker's decision making capability and ability to tolerate some type of defects are the main reasons for several firms to still rely on human visual inspection. Further, it is believed that the investment and maintenance costs of the automated systems may be higher than labour costs. This study considers a ceramic tile line where workers are assigned to identify tile surface defects. Main aim is to attract attention to differences between novice and expert workers in terms of visual scanning performance and mental workload indicators that result from high concentration during visual inspection. A mobile type eye-tracker is used to record the data for duration of fixation and number of fixations to determine fatigue that arises over a period of working time. Data are analysed and it is concluded that the eye tracking systems have a potential to identify human related problems during visual inspection.